TAXONOMIA E FILOGENIA DE Urtica L. (URTICACEAE Juss.) OCORRENTES NO BIOMA MATA ATLÂNTICA - Rodrigues, Carine Muniz (2019)
Urtica L. is the largest genus of the Urticeae Lam. & DC. tribe (Urticaceae Juss.), with a diversity center in Asia and Europe, and has nearly 30 species for the Neotropical region. This genus lacks of recent studies that explains its evolution and taxonomy, mainly Atlantic Forest species. This biome is considered a global hotspot, due to its high biodiversity and presence of endemic species, which has been threatened by anthropogenic actions. Therefore, the aim of this study was to characterize taxonomically and phylogenetically the Urtica species from the Atlantic Forest. Taxonomic analyses were performed based on herborized materials, through visits to national herbariums, and virtual platforms. Furthermore, reference studies of this group were consulted. New materials collected during the research were deposited in the herbarium SP, RB, EVB and in the botanical collection ARAUCA. For the phylogenetic analyses, samples from the Atlantic Forest were sequenciated, using plastidial and nuclear markers. The phylogenetic tree was constructed with Atlantic Forest sequences for Urtica L, besides other accesses obtained from the GenBank. Taxonomic results attained the occurrence of the following species to Atlantic Forest biome: Urtica circularis (Hicken) Sorarú, U. dioica L, U.spathulata Sm. and U.urens L. An identification-key was created for these species, also morphological, distribution and ecological descriptions and taxonomic comments were carried out. The phylogenetic tree presented Urtica as a paraphyletic, with the species found in the Atlantic Forest being approximate to other South American species. The Morphological data and geographic distribution of the species found in this biome are informative to explain their phylogenetic relationship.